PENGARUH RENTABILITAS, SOLVABILITAS, DAN MANAJEMEN ASET TERHADAP KINERJA KEUANGAN PERUSAHAAN SUBSEKTOR PERDAGANGAN BESAR YANG TERDAFTAR DI BEI - Rosa Mustika Putri; Mulyaningtyas Mulyaningtyas (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
To determine the performance of an entity, several efforts were made, one of which was by conducting research on financial profitability ratios, financial solvency ratios, and financial asset management ratios. Purposive sampling is the testing strategy chosen in this research, with the research population being large trading sub-sector companies listed on the IDX for the period 2018 - 2020. The specimen data selected in this study were 15 companies. Descriptive statistical analysis was used to test the specimens, and multiple regression analysis was used to test the feasibility of the model. According to the results of this research, the profitability variable on the projection with ROE has a positive effect on financial performance on the projection with Return on Assets, the solvency variable projected on DAR has a significant and negative effect on the company's financial performance, while asset management projected with TATO does not have a major impact on the company's financial performance. company's financial performance.